Public spaces and children's learning in children aged 2 to 8 years old in Metropolitan Lima, 2023. - Gonzales Palma, Josselyne Denise (2024)
The objective of the study presented was to determine the relationship between public spaces and children's learning in children from 2 to 8 years old in Metropolitan Lima area during the year 2023. The methodology for this research corresponded to the quantitative study, being of a basic type with the application of non-experimental and correlational design. According to the results of the hypothesis testing, it is likely that the two variables of the study collected are not correlated. It is advisable to continue with this study in the municipalities not intervened and expand the consultation coverage to the teachers of UGEL 3 and UGEL 7; as well as establishing in the following milestones of this research a strengthening program aimed at municipal officials and teachers of Educational Institutions that have more critical results regarding the relationship of the variables of this research in Metropolitan Lima.